THE EFFECT OF RETURN ON EQUITY AND DEBT TO EQUITY RATIO ON SHARIA STOCK RETURN WITH INSTITUTIONAL OWNERSHIP AS A MODERATING VARIABLE - Ramadhanti, Tiara Zulfina; Mardi; Ulupui, I.G.K.A (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
Before making an investment, an investor must seek as much information as possible from the intended company so that the investment can provide a high return. This activity can be done with fundamental analysis. This study aims to determine the effect of Return on Equity and Debt to Equity Ratio on Sharia Stock Returns with Institutional Ownership as Moderating Variables. The study used a quantitative approach with multiple linear regression analysis and moderated regression analysis using Eviews version 12 software. The population in this study were companies registered on the Jakarta Islamic Index (JII) 70 in 2022 and the sample used was 44 companies using a purposive sampling technique. The results of this study indicate that ROE has a significant positive effect on sharia stock returns because the higher the ROE value, the sharia stock return value also increases. Then, DER has a significant negative effect on sharia stock returns because the higher the DER value, the sharia stock return value will decrease. Institutional ownership weakens the effect of ROE on sharia stock returns because strong control can make many decisions regarding company finances which can reduce the amount of profit and the composition of the company's shares/equity. Institutional ownership does not moderate the effect of DER on sharia stock returns because companies with high institutional ownership are unable to convince investors of the company's performance in managing its debt.